(untitled) (International Journal on Stereo & Immersive Media, 2025)
This article delves into the complexities surrounding the Panorama of Congo, a challenging object of inquiry due to its exceptional size and contentious historical context. Commissioned by the Belgian Ministry of Colonies in 1913 to promote the Belgian Congo, the painting raises critical questions about colonial legacies amidst contemporary debates on decolonisation. Utilising artistic research as a central methodological tool, the FilmEU RIT Congo VR project explores the broader cultural issues hidden within this heritage object. Through a transdisciplinary approach, integrating artistic, media archaeological, and postcolonial perspectives, the research investigates the imperialist implications of immersive media, particularly panoramas, and the role of Virtual Reality in reinterpreting their embedded historical narratives. Highlighting the Congo VR project, the article showcases artistic creations and installations presented in exhibitions, emphasising the convergence of artistic research and decolonial approaches within museum contexts. This research contributes to a nuanced understanding of colonial heritage and its implications for contemporary discourse on cultural representation and memory.